2020
DOI: 10.1098/rstb.2019.0565
|View full text |Cite
|
Sign up to set email alerts
|

Helping decisions and kin recognition in long-tailed tits: is call similarity used to direct help towards kin?

Abstract: Most cooperative breeders live in discrete family groups, but in a minority, breeding populations comprise extended social networks of conspecifics that vary in relatedness. Selection for effective kin recognition may be expected for more related individuals in such kin neighbourhoods to maximize indirect fitness. Using a long-term social pedigree, molecular genetics, field observations and acoustic analyses, we examine how vocal similarity affects helping decisions in the long-tailed tit Aegithalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 73 publications
2
18
0
Order By: Relevance
“…Indeed, this suggests a mechanism of phenotype matching, with a gradation of similarity in vocalizations providing a fine-grained, continuous estimation of kinship. However, bioacoustic analysis did not support this suggestion (Leedale et al, 2020), so even in this relatively well-studied system, the mechanism underlying graded discrimination remains unknown.…”
Section: Familiaritymentioning
confidence: 78%
See 4 more Smart Citations
“…Indeed, this suggests a mechanism of phenotype matching, with a gradation of similarity in vocalizations providing a fine-grained, continuous estimation of kinship. However, bioacoustic analysis did not support this suggestion (Leedale et al, 2020), so even in this relatively well-studied system, the mechanism underlying graded discrimination remains unknown.…”
Section: Familiaritymentioning
confidence: 78%
“…Long-tailed tits have a kinselected cooperative breeding system in which failed breeders preferentially redirect their care to help relatives (Russell and Hatchwell, 2001;Hatchwell et al, 2014). Playback experiments show that long-tailed tits are able to discriminate between the calls of close kin and non-kin (Hatchwell et al, 2001;, and the calls thought to be used as recognition cues are individually distinctive, repeatable and more similar among close kin than among non-kin Leedale et al, 2020). Cross-fostering experiments showed that nestlings and/or fledglings acquire their recognition templates from familiar kin during an associative learning period, when the cues themselves develop , and that cross-fostered offspring subsequently help at the nest of foster siblings (Hatchwell et al, 2001).…”
Section: Familiaritymentioning
confidence: 99%
See 3 more Smart Citations